RETRACTED: Modeling of light transmission in multilayer epitaxial AlN/GaN structures for biomedical pyrosensors - Panyutin Eugeny; Ilicheva Tatiana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001